Endobronchial Tuberculosis - (:unkn) unknown (KARGER, 2010)
Childhood tuberculosis (TB) is characterized by enlarged mediastinal lymph nodes which compress and infiltrate the airways resulting in endobronchial tuberculosis (ETB). ETB has been reported in 41-63% of children suspected of pulmonary TB. In children the disease is typically pausibacillary, which hinders the microbiological confirmation of the diagnosis. Flexible bronchoscopy (FB) is a useful tool for the confirmation of paediatric ETB. Indications for performing FB in children suspected of having TB include: confirmation of the diagnosis, determination of the degree of airway compression in children with radiological evidence of airway obstruction, management of life-threatening airway obstruction and evaluation of the response to treatment. Common bronchoscopic presentations of ETB are airway compression (42-59%) and TB lymph node ulceration into the airway (18-29%). The most commonly involved site is the right main bronchus. The bronchoscopic presentation of ETB in HIV-positive and HIV-negative children does not differ. The diagnostic yield of the microbiological analysis of bronchoalveolar lavage fluid in childhood pulmonary TB is greatly enhanced when taking into account the endobronchial abnormalities that are detected by endoscopy. The diagnostic value of endobronchial and/or transbronchial biopsy has not been reported. Copyright (C) 2010 S. Karger AG, Basel
Keywords: FOREIGN-BODY ASPIRATION; CHILDHOOD PULMONARY TUBERCULOSIS; FLEXIBLE BRONCHOSCOPY; MYCOBACTERIUM-TUBERCULOSIS; BRONCHOALVEOLAR LAVAGE; CHILDREN; DIAGNOSIS; CORTICOSTEROIDS; LYMPHADENOPATHY; INVOLVEMENT